Performance Changes Following Top Management Dismissals - DENIS, DAVID J.; DENIS, DIANE K. (Journal of Finance, 1995)
ABSTRACT We document that forced resignations of top managers are preceded by large and significant declines in operating performance and followed by large improvements in performance. However, forced resignations are rare and are due more often to external factors (e.g., blockholder pressure, takeover attempts, etc.) than to normal board monitoring. Following the management change, these firms significantly downsize their operations and are subject to a high rate of corporate control activity. Normal retirements are followed by small increases in operating income and are also subject to a slightly higher than normal incidence of postturnover corporate control activity.